Pemeliharaan Laboratorium IPA di MTs Negeri 1 Kota Palembang - Winada, Annisa; Zulkipli, Zulkipli; Syahputra, Ade Akhmad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Science laboratory maintenance constitutes an essential component of educational facilities management that plays a significant role in enhancing the effectiveness of science learning in madrasahs. A well-maintained laboratory provides a safe, organized, and conducive learning environment that supports students’ competency development through practical activities. This study aims to describe the implementation of science laboratory maintenance at MTs Negeri 1 Kota Palembang and to analyze the supporting and inhibiting factors affecting its management. This research employed a descriptive qualitative approach. Data were collected through non-participant observation, semi-structured interviews, and documentation. The informants consisted of the head of the laboratory, the vice principal in charge of facilities and infrastructure, science teachers, and students. Data were analyzed through data reduction, data display, and conclusion drawing, while validity was ensured through source, technique, and time triangulation. The findings indicate that laboratory maintenance has been implemented through awareness building, understanding, organizing, implementation, and data recording. However, the system has not yet been fully structured due to the absence of formal Standard Operating Procedures (SOP), scheduled preventive maintenance programs, and a digital inventory system. Supporting factors include teachers’ commitment and adequate facilities, while inhibiting factors involve limited budget allocation and the absence of a dedicated laboratory technician. Strengthening systematic and sustainable maintenance management is therefore necessary to optimize science learning outcomes.